Pengaruh Orientasi Kewirausahaan dan Kreativitas Produk Terhadap Keunggulan Bersaing pada Pelaku Usaha Sentra Wisata Kuliner Convention Hall Keputih di Surabaya - Yulianti, Dita; Pujianto, M.M, Drs. Agung; Nasution, M.S, Drs. Ute Chairuz (Research Journal of Social Science and Economics, 2025)
The research aimed to investigate the influence of entrepreneurial orientation and product creativity on competitive advantage among businesses in Keputih Culinary Tourism Convention Hall in Surabaya. A quantitative method using a survey with a questionnaire was employed to collect data. The study had 40 respondents, selected through non-probability sampling using saturation sampling technique, where all population members were included as samples. Multiple regression analysis was utilized for data analysis. The research sample comprised business operators in Keputih Culinary Tourism Convention Hall. Data analysis methods included multiple linear regression analysis, determination coefficient R2, and hypothesis testing (t-test and F-test). The findings demonstrated that both entrepreneurial orientation and product creativity have a positive and significant influence on competitive advantage, both partially and overall. Keywords: Entrepreneurial Orientation, Product Creativity, Competitive Advantage